Reading The Waste Land from the Bottom Up - Booth, A. author. aut Link
XIX, 273 p.
Keywords: A guidebook to the allusions of T.S. Eliot's notorious poem, The Waste Land , Reading The Waste Land from the Bottom Up utilizes the footnotes as a starting point, opening up the poem in unexpected ways. Organized according to Eliot's line numbers and designed for both scholars and students, chapters are free-standing and can be read in any order.